65.7k views
5 votes
Drag the tiles to the correct boxes to complete the pairs.

Drag the tiles to the correct boxes to complete the pairs.-example-1
User Cjs
by
4.4k points

1 Answer

3 votes

Answer::


\begin{gathered} q(x)=x^2-4x+1 \\ r(x)=0 \\ b(x)=x-3 \end{gathered}

Explanation:

Given the quotient:


(x^(3)-7 x^(2)+13 x-3)/(x-3)

We want to rewrite the quotient in the form:


q(x)+(r(x))/(b(x))

First, we use the long division method to first divide.

Therefore:


(x^(3)-7x^(2)+13x-3)/(x-3)=x^2-4x+1+(0)/(x-3)

We thus have the following:


\begin{gathered} q(x)=x^2-4x+1 \\ r(x)=0 \\ b(x)=x-3 \end{gathered}

Drag the tiles to the correct boxes to complete the pairs.-example-1
User Pramod Shinde
by
5.2k points